Epidemiology of Microbial Keratitis in a Tertiary Care Center in Karachi - Aziz ur Rehman, Mazhar ul Hasan, Qamar Riaz, Umar Fawwad, Nasir Bhatti (Pakistan Journal of Ophthalmology, 2013)
Purpose: To measure the frequency, etiology and outcome of management of microbial keratitis in a tertiary care center in Karachi. Material and Methods: A prospective analysis of 133 cases clinically diagnosed as microbial keratitis at Al Ibrahim Eye Hospital in Karachi over an 8 month period from 1st February to 31st September 2010, was performed. A standardised form was filled out for each patient, documenting sociodemographic features and information pertaining to ocular or systemic risk factors, management, microbiological tests and visual outcomes. Corneal scrapes were collected and subjected to microscopy / staining, culture and sensitivity. Viral ulcers, Mooren’s ulcer and ulcer associated with systemic or autoimmune diseases were excluded from the study. Results: Males (63.2%) were affected more than the females. The most common predisposing cause of ulceration was corneal trauma (48%), usually with organic agricultural materials and most frequent diagnosis was fungal keratitis (63%). Of the 68 (51.1%) patients who were followed up till the end of the treatment, visual outcome improved in 30 (44.1%), remained same in 15 (22.1%) while worsened in 23 (33.8%) patients. Conclusion: Microbial keratitis continues to be a frequent cause for concern among ophthalmologists and health managers. This study will serve as local epidemiological database regarding microbial ulcers as well as help us in formulating guidelines for prevention of suppurative keratitis in the population at risk.